Didactics for the teaching of mathematics through the seminars workshops intelligent games - Chacón Benavides, José Antonio; Fonseca Correa, Luis Ángel (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This article aims to describe new pedagogical practices for the teaching of mathematics because it has been assuming through the time a rigidly rules and concepts focused on algorithmic development, forgetting significant aspects in the process of learning mathematics. It starts with a description of the didactics of mathematics, as well as the game as a pedagogical strategy to make the teaching and learning of mathematics an intentional process of appropriation of mathematical knowledge. At the same way, it announces from the teaching experience the realization of seminars about smart games in order to deepen the mathematical background of each of the materials used support.